2017
DOI: 10.1177/0888406417727041
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Model of Learning and Transfer: A Review of Instructional Methods and Learning Outcomes in Special Education Teacher Preparation

Abstract: In the past decade and a half, measurable outcomes of teacher performance and student achievement have moved to the forefront of education policy. Researchers have identified a gap in special education teacher preparation research and have called for the re-envisioning of current educational models, emphasizing a focus on effective methods in special education teacher preparation. Prior studies and literature reviews have demonstrated a need for experimental research on effective methods that move preservice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…(2017) regarding training methods for special education practitioners found BST was “associated with the most consistent improvement in implementation fidelity” (p. 21). Within teacher preparation, Juarez and Purper (2018) have called for more research regarding how universities are instructing preservice teachers on content knowledge and implementation. The components of BST are not unfamiliar to teacher educators.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) regarding training methods for special education practitioners found BST was “associated with the most consistent improvement in implementation fidelity” (p. 21). Within teacher preparation, Juarez and Purper (2018) have called for more research regarding how universities are instructing preservice teachers on content knowledge and implementation. The components of BST are not unfamiliar to teacher educators.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of learners' academic abilities has been described as a significant variable linked to successful instruction preparation and positive learning outcomes [26]. B. K. Martens & J. C. Witts [14] concluded that, with the exception of an adequate evaluation of the academic skills of learners, instructional judgment is unlikely to promote academic competence.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Assessment for Learning incorporates assessment into the teaching process by helping students understand precisely what they need to learn, what is required of them and offering input and guidance on how to enhance their work through the use of certain enhanced assessment methods [26]. Assessment for Learning is concerned with the act of collecting evidence about learning that encourages feedback through some assessment methods like rubrics, portfolios, achievement -based assessment, self-assessment and peer-assessment, which are aimed at adapting to teaching and plan next steps in learning [13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, limited research has been conducted on how to best prepare special education teachers (Brownell et al, 2020; Juarez & Purper, 2018; Sindelar et al, 2010). It is clear, as illustrated in the RCM, development of a teacher’s PCK involves numerous knowledge bases that take time to develop—often beyond the time available in a teacher preparation program; however, one highly recommended teacher preparation practice for the development of these knowledge bases is through deliberate opportunities to practice along with support and valuable feedback (Benedict et al, 2016; Brownell et al, 2019; Leko et al, 2015).…”
Section: Preparing Pre-service Teachers To Use Vrs In Their Mathematics Instruction (Ppck and Epck)mentioning
confidence: 99%